VERTEBRAL DEVELOPMENT AND PROTEASE ACTIVITY OF LARVAL MILKFISH, Chanos chanos Forsskal IN DIFFERENT REARING MEDIA - Titiek Aslianti; Afifah Nasukha; Irwan Setyadi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
The milkfish (Chanos chanos Forsskal) seed quality is an important factor for supporting the fisheries industrialization program . The egg fertility and larval rearing management are two main factors to improve the quality of the seed. The aim of this research was to obtain the information about those two indicators on milkfish larvae, reared in different media. About 100,000 eggs were located in 6 units of the outdoor concrete tank with volume of 6 m3. Larvae were reared due to the rearing standard procedure while the feeding management was adapted during larvae development. Two different treatments in larval rearing medium were with and without the addition of molasses, subsequently in triple trials. This study started from hatching day (0 DAH) until the end of larval rearing period (16-18 DAH). The growth parameters such as vertebrae analyses and survival were taken in the end of research periods, while protease assessment was analyzed every day using tyrosine and casein standard methods. The results showed that the molasses addition produced a higher growth (TL 12.95±0.87 mm) and survival rate (87.66±1.52%), better vertebral performance (44-45 segments), and higher protease activity (0.1392-0.3863 U/ml/min) than without molasses addition. The results indicated that molasses addition in larvae rearing medium improved the larvae quality. Keywords: Protease enzime activity,milkfish seeds, molasses, vertebrae